Complement Inhibition Targeted to Injury Specific Neoepitopes Attenuates Atherogenesis in Mice - Dai, Shen; Liu, Fengming; Ren, Mi; Qin, Zhongnan; Rout, Namita; Yang, Xiao-Feng; Wang, Hong; Tomlinson, Stephen; Qin, Xuebin (Frontiers in Cardiovascular Medicine, 2021)
Rationale: Previous studies have indicated an important role for complement in atherosclerosis, a lipid-driven chronic inflammatory disease associated to oxidative stress in the vessel wall. However, it remains unclear how complement is activated in the process of atherogenesis. An accepted general model for complement activation in the context of ischemia reperfusion injury is that ischemia induces the exposure of neoepitopes that are recognized by natural self-reactive IgM antibodies, and that in turn activate complement. Objective: We investigated whether a similar phenomenon may be involved in the pathogenesis of atherosclerosis, and whether interfering with this activation event, together with inhibition of subsequent amplification of the cascade at the C3 activation step, can provide protection against atherogenesis. Methods and Results: We utilized C2scFv-Crry, a novel construct consisting of a single chain antibody (scFv) linked to Crry, a complement inhibitor that functions at C3 activation. The scFv moiety was derived from C2 IgM mAb that specifically recognizes phospholipid neoepitopes known to be expressed after ischemia. C2scFv-Crry targeted to the atherosclerotic plaque of Apoe-/- mice, demonstrating expression of the C2 neoepitope. C2scFv-Crry administered twice per week significantly attenuated atherosclerotic plaque in the aorta and aortic root of Apoe-/- mice fed with a high-fat diet (HFD) for either 2 or 4 months, and treatment reduced C3 deposition and membrane attack complex formation as compared to vehicle treated mice. C2scFv-Crry also inhibited the uptake of oxidized low-density-lipoprotein (oxLDL) by peritoneal macrophages, which has been shown to play a role in pathogenesis, and C2scFv-Crry-treated mice had decreased lipid content in the lesion with reduced oxLDL levels in serum compared to vehicle-treated mice. Furthermore, C2scFv-Crry reduced the deposition of endogenous total IgM in the plaque, although it did not alter serum IgM levels, further indicating a role for natural IgM in initiating complement activation. Conclusions: Neoepitope targeted complement inhibitors represent a novel therapeutic approach for atherosclerosis.